Myo-inositol ameliorative effects on cryo-survival of post-thawed abnormal human sperms quality towards infertility care - Abdul Wahab, Azantee Yazmie; Ahmad Yusof, Zamri; Abdul Rahman, Suzanah; Md Isa, Muhammad Lokman; Mazlan, Muhammad Alif (2023)
Background Sperm cryopreservation usually results in a significant decrease in sperm quality after thawing. The deleterious effects of freeze-thaw on abnormal sperm samples are considerably more severe. Various supplemental agents have been studied to ameliorate the negative effects due to cryopreservation. Myo-Inositol is likely to positively affect fertility. Therefore, this study aims to evaluate the beneficial effect of Myo-inositol (MI) supplementation in sperm freezing media for abnormal sperm. Methods Semen samples were collected from 23 male subjects that have abnormal sperm quality. Semen analysis has been conducted before freezing (pre-freeze). The samples were frozen with only a freezing medium (control) or MI-supplemented freezing medium. Semen analysis was re-evaluated after post-thaw for both groups. GoldCyto test kits were used in both post-thaw samples to evaluate the DNA fragmentation. Results The total motility, Progressive motility, morphology, and viability mean values of the sperms frozen with the MI-supplemented medium are greater compared to the control group (p<0.05). The post-thaw sample with MI supplementation (39.8%) has a higher cryo-survival rate (CSR) compared to the control group (23.4%). Conclusion MI supplementation in cryopreserved abnormal sperm samples significantly enhanced the post-thaw sperm motility, morphology, and vitality, and potentially increase the sperm survival rate.